The effects of sodium chloride ingestion on fluid balance and body fluid distribution during exercise - Sanders, Barry (MRC/UCT RU for Exercise and Sport Medicine, 2018)
The aim of the first experiment of this thesis was to determine whether the ingestion of a concentrated sodium chloride solution (100mEq/1) during exercise would expand the plasma volume when fluid was ingested at approximately half the rate at which it was being lost as sweat. Six male cyclists exercised for 90 minutes in the heat (32 ± 1 °C, 55 ± 5% RH) at 66 ± 1 % of VO₂ₘₐₓ while ingesting either no fluid CNF), water (W), or a saline CS) solution (100mEq/1). In the Wand S trials, subjects drank 400ml of the fluid immediately prior to commencing exercise, and 100ml of fluid every 10 minutes during exercise until 80 minutes. In the S trial sodium chloride was ingested in capsules. One capsule containing 0.585g of sodium chloride was ingested with every 100ml of water. At the end of the 90 minute exercise bout they rested in a sitting position for one hour in cool conditions (22 ± 1 °C and 70 ± 5% RH). After the initial drop in plasma volume due to the onset of exercise. plasma volume decreased progressively during the NF trial and was significantly less than the 10 minute value at 80 and 90 minutes (p<0.0033). At 40, 60, 80 and 90 minutes of exercise, the plasma volume in the NF trial was significantly less than in the W and the S trials (p<0.05). There was no significant difference between the W and the S trials at any time. Further, after the initial drop in plasma volume due to the onset of exercise. plasma volume did not decrease any further in either the W or the S trial. Plasma sodium concentrations in the NF and the S trial were significantly elevated at 40, 60, 80 and 90 minutes (p<0.0033). Plasma sodium concentration in the NF and the S trials were also significantly higher than in the W trial at 80 and 90 minutes of exercise (p<0.05). Since the ingestion of a sodium chloride solution containing 100mEq/1 did not have a beneficial effect on plasma volume and plasma sodium concentration, when fluid ingestion rates were approximately half of the rate of sweat loss, it is concluded the under these conditions, the ingestion of a concentrated sodium chloride beverage has no advantage over the ingestion of water. The aim of the second experiment of this thesis was to determine the effect of varying concentrations of sodium chloride ingestion on fluid balance, when the rate of fluid ingestion matched the sweat rate. Six male cyclists cycled for 4 hours at 55% of VO₂ₘₐₓ in mild conditions (20 ± 1°c and 70 ± 5% RH), while ingesting either a low salt (LS) (4.6 mEq/1), a medium salt (MS) (50 mEq/1) or a high salt (HS) (100 mEq/1) beverage. Each beverage also contained a glucose polymer in an 8% concentration (8g/100ml). The subjects ingested 400ml of beverage immediately prior to commencement of exercise, and 150ml of fluid every 10 minutes during exercise until 220 minutes. Sodium chloride in the MS and HS trials was given to the subjects as supplemental gel capsules so that the drink was palatable. At the end of exercise, subjects recovered in a sitting position for 30 minutes. At the end of the 4 hours of exercise, fluid loss via the urine was significantly greater in the LS and the MS trials than in the HS trial (p<0.05). As a result, the fluid deficits in the LS and the MS trials were significantly greater than the fluid deficit in the HS trial. There was no significant difference between the MS and the LS trials for urinary fluid loss. During the 4 hour exercise bout, plasma sodium concentrations in the LS, the MS and the HS trials were not significantly different from one another, nor were they significantly different from resting values. There was no significant difference in the rectal temperature response to exercise in the three trials. It can therefore be concluded that in conditions where fluid ingestion matches sweat rate, attenuation of urinary fluid loss to optimise fluid replacement, relies on the ingestion of sodium chloride in quantities greater than that lost in the sweat. Therefore, for the ingestion of sodium chloride in excess of that which is currently available in sports drinks to beneficial, fluid must be ingested in volumes matching sweat loss.